Dystocia due to fetal muscular hypertrophy and excessive accumulation of abdominal fat in a buffalo fetus - PRABHAKAR, S; GANDOTRA, V K; HONPARKHE, M (The Indian Journal of Animal Reproduction, 2003)
A rare case of dystocia due to muscular hypertrophy and excessive deposition of fat in abdominalcavity of fetus was relieved by partial fetotomy.
Keywords: Dystocia; muscular hypertrophy; fetal oedema